2024
DOI: 10.3390/ijms25073591
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action of Dorsal Root Ganglion Stimulation

Alaa Abd-Elsayed,
Swarnima Vardhan,
Abhinav Aggarwal
et al.

Abstract: The dorsal root ganglion (DRG) serves as a pivotal site for managing chronic pain through dorsal root ganglion stimulation (DRG-S). In recent years, the DRG-S has emerged as an attractive modality in the armamentarium of neuromodulation therapy due to its accessibility and efficacy in alleviating chronic pain refractory to conventional treatments. Despite its therapeutic advantages, the precise mechanisms underlying DRG-S-induced analgesia remain elusive, attributed in part to the diverse sensory neuron popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…DRG neurons are pseudo-unipolar cells that bridge the gap between peripheral tissues and the spinal cord, delivering their products through their two nerve endings, with implications in both the PNS and CNS [ 59 , 60 ]. Using a model of tibial nerve injury in rats and DRG stimulation at the L 4 level, replicating a clinically used load (20 Hz, 150-ms pulse width, current at 80% of motor threshold), it was shown that cold and mechanical hyperalgesia and allodynia were reduced [ 61 ].…”
Section: Neuromodulation Therapies Targeting Drg and The Spinal Cord ...mentioning
confidence: 99%
See 2 more Smart Citations
“…DRG neurons are pseudo-unipolar cells that bridge the gap between peripheral tissues and the spinal cord, delivering their products through their two nerve endings, with implications in both the PNS and CNS [ 59 , 60 ]. Using a model of tibial nerve injury in rats and DRG stimulation at the L 4 level, replicating a clinically used load (20 Hz, 150-ms pulse width, current at 80% of motor threshold), it was shown that cold and mechanical hyperalgesia and allodynia were reduced [ 61 ].…”
Section: Neuromodulation Therapies Targeting Drg and The Spinal Cord ...mentioning
confidence: 99%
“…DRG neuromodulation therapy emerged later than traditional SCS as an alternative approach. DRG stimulation is effective across a range of frequencies, with 20 Hz being the default frequency [ 59 ]. In one of the first clinical trials evaluating DRG stimulation for the management of neuropathic pain, the patient population presented with neuropathies associated with intractable pain in the back and lower limbs.…”
Section: Neuromodulation Therapies Targeting Drg and The Spinal Cord ...mentioning
confidence: 99%
See 1 more Smart Citation